Ball burnishing - Loh, Ngiap Hiang (2008)
The characteristics of ball burnishing as a surface finishing process is reported here. The effects of ball burnishing parameters on the surface finish and hardness of plano AISI 1045 steel have been studied using conventional and statistical (eg factorial design techniques.